Charge measurements for optimised NOM characterisation and removal by coagulation - Ruth, Daniel; Jefferson, Bruce; Pereira, Ryan; Moore, Graeme; Jarvis, Peter (Elsevier, 2026)
Climatic changes have altered natural organic matter (NOM) characteristics in raw water, intensifying challenges for operation of water treatment systems, particularly the coagulation process. This study explored the measurement of water charge characteristics, in parallel with a range of water quality parameters over an extensive year-long sampling campaign. Results showed variable charge load (15–197 μEq/L) in the raw water throughout the year, attributed to dynamic humic-organic carbon concentrations (1.1–8.3 mg/L) coinciding with increased average rainfall (2.4 mm/day to 6.1 mm/day). Coagulation tests showed a stronger linear relationship between charge load and coagulant demand than for dissolved organic carbon (DOC) concentration (R2 = 0.80 vs 0.65). This was because the charge characteristics of the water did not change in a consistent way with the NOM concentration, meaning that bulk indicators of organic matter concentration (DOC and UV254) were not always effective for predicting the appropriate coagulant dose. Post-coagulation zeta potential analysis showed minimised DOC residuals at a zeta potential between −10 and 5 mV, with maximum removal achieved when the average zeta potential approached 0 mV. Analysis of the zeta potential distribution provided a new understanding of ideal operating conditions for coagulation. Median zeta potential of −1.69 mV resulted in a condition where at least 68% of all particles were within a range that was effective for charge neutralisation. The study highlights the importance of refining coagulation control methods to address climate-influenced NOM changes, recommending the adoption of UV254 coupled with zeta potential as feed-forward and feedback systems, respectively, to provide optimal DOC removal by coagulation.
Keywords: 40 Engineering; 4004 Chemical engineering; 4005 Civil engineering; 4011 Environmental engineering; Charge; coagulation; natural organic matter; zeta potential